A simplified globally affordable experimental setup for monitoring DNA diagnosis by a QD-based technique - Rostam Gohari, Samira; Yazdanparast, Razieh (Folia microbiologica, 2018)
The unavailability of simple, quick, and sensitive genetic-based molecular diagnostic techniques has become the main driving force for inventing new approaches in the era of quantum dots (QDs): a new class of fluorescent probes with fascinating optical electronic properties. Using the unique size-dependent light-emitting properties of QDs, we have developed a QD-based ultrasensitive technique which removes the necessity for the genetic amplification step required in almost all types of molecular-based diagnostic techniques. The selectivity of the new approach is warranted by the careful design of a pair of specific oligonucleotide probes, chemically modified at their 5'-ends. Our results indicated the selective detection of Salmonella typhi in an assay time of 50 min with a limit of detection (LOD) of 2 CFU/mL. The rapidity, selectivity, and sensitivity and the low assay cost make the new diagnostic technique a promising new tool for laboratory and field-based approaches to molecular diagnosis of health-threatening pathogens. Graphical abstract.
Keywords: oligonukleotidové sondy; Limit of Detection; Humans; kvantové tečky; DNA, Bacterial; Oligonucleotide Probes; lidé; Quantum Dots; limita detekce; Fluorescent Dyes; Molecular Diagnostic Techniques; Typhoid Fever; diagnostické techniky molekulární; Salmonella typhi; fluorescenční barviva; DNA bakterií; břišní tyfus